Technique For Teaching Speaking At The Seventh Grade Of SMP Negeri 1 Sambi In 2016/2017 Academic Year - Rindy Aswary, Tiara, Drs. Djoko Srijono, M.Hum (2016)
This research aims to describe the technique for teaching speaking at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year. The objectives of the research are to describe the technique for teaching speaking process at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year and to describe the advantages and disadvantages of technique for teaching speaking faced by the teacher at the seventh grade of SMP Negeri 1 Sambi in 2016/2017 academic year. This research uses descriptive study. The subject of the research focuses on English teachers of seventh grade of SMP Negeri 1 Sambi. In collecting the data, the researcher uses observation, document analysis, and interview. The collected data are analyzed by collecting, reducing, and displaying data, classifying and verifying the data, and drawing conclusion. Based on the research finding, it was found that the technique for teaching speaking related to the process of explanation, repetition, manipulation, reproduction, discussion, and presentation. It was always done by the teacher in every teaching activity. The advantages of techniques are that teacher feels comfortable in teaching activity and assessing students' score. Teacher can also find the students whether active and understand or not. Then the disadvantages of the techniques are that the lack of time for guiding a lot of students. The teacher feels difficult in managing the students. Keywords: teaching technique, teaching speaking